An Investigation into the Impact of Managerial Overconfidence, Real Earnings Management, and Enterprise Risk Management on Corporate Social Responsibility - Pourmansouri, Rezvan; Damoori, Dariush; Fallah, Mir Feiz; Dekamini, Fatemeh; Birau, Ramona (International Journal of Economics and Financial Issues, 2025)
Corporate social responsibility (CSR) has emerged as a new and sensitive topic in the theoretical literature of accounting research. It is considered a fundamental factor for the survival of companies and has attracted attention from various perspectives of investors, managers, and researchers. Researchers have identified numerous variables as influential factors in CSR. However, this study specifically focuses on examining factors such as Enterprise Risk Management (ERM), Real earnings management (REM), and CEO overconfidence in relation to CSR. This research used data related to 121 companies listed on the Tehran Stock Exchange (TSE) from 2010 to 2022. The results of the hypotheses in this study indicate that when a company lacks an appropriate risk management mechanism (with more unconventional risk management), the level of CSR is lower. Alternatively, managers with higher overconfidence are motivated and inclined to manipulate real earnings. They may endeavor to justify their misuse of company financial resources under the pretext of fulfilling CSR.